Square-root optimal hankel norm approximation technique for order reduction of non-minimal systems - Kumar D.; Nagar S.K. (My University, 2025)
This paper intends to the development of order reduction technique for reduction of non-minimal systems which is a combination of square-root approach and schur decomposition algorithm. The proposed technique alleviates the practical difficulties in computations of balancing transform for non-minimal systems. A numerical example is considered to validate the proposed algorithm and the comparison with other well known techniques shows the effectiveness of the proposed algorithm. © 2014 IEEE.